Pengaruh Pemahaman Wajib Pajak, Kualitas Pelayanan, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak - Marchya Monica; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
This study aims to examine the effect of taxpayer understanding, service quality, and tax sanctions on taxpayer compliance. This research was conducted the Cakung Dua area by using the convenience sampling method using primary data. This research uses descriptive research with a quantitative approach by processing questionnaire data using multiple regression analysis methods with the SPSS 26 application. The population of this study is an individual taxpayer in the Cakung Dua area so that a sample of 100 respondents was obtained. The results of this study indicate that the understanding of taxpayers and tax sanctions have a positive effect on taxpayer compliance. As for service quality has no effect on taxpayer compliance.